Sharing fact checking corrections in polarized political environments: A study of context and disambiguation - Natalia Aruguete; Ernesto Calvo (Revista Internacional de Sociología)
Social media platforms have long been considered a source of polarization. They are also considered a key mechanism for amplifying misinformation and spreading false, distorted, and decontextualized information. In such polarized environments, fact-checking interventions are of the utmost importance. This article aims to understand whether polarizing partisan messages also hinder the circulation of fact-checking corrections. Specifically, we test whether exposure to polarizing political messages next to fact-checking messages alters the propensity of users to share messages (destructive interference) or increases their circulation (constructive interference). Using a survey experiment conducted in Argentina during the National Midterm Election of 2022, we measure the propensity to share fact checks when placed alongside partisan messages. Our results show that polarizing political messages increase the propensity to share fact checks (constructive interference) instead of reducing circulation. This is a positive outcome, demonstrating that interventions to reduce the spread of misinformation are more likely to be shared in partisan political environments. Therefore, while polarization increases the rate at which misinformation is produced, it may also facilitate the circulation of its corrections.